How landscape ecology can promote the development of sustainable landscapes in Europe – The role of the european association for landscape ecology (IALE Europe) in the 21st century - Antrop, M. (2014)
In Europe, landscape research has a long tradition of drawing on several disciplines. ‘National schools’ of landscape research developed, which were related to the characteristic landscapes found in the different countries and to specific linguistic meanings and legal traditions when using landscape related concepts. International co-operation demands a certain harmonization of these concepts for better mutual understanding. The 2000 European Landscape Convention provided an important momentum to rethink research, policy and management of landscapes from the perspective of sustainable development and participatory planning. Landscape ecology as a transdisciplinary science with a dynamic and holistic perspective on landscape offers a great potential for an integrative approach. The specificity of the European landscape research rests on its long history and on integration based on the great diversity of the landscapes, characterised by an intimate relationship between the varied natural environment and the different cultural traditions which define the identity of countries, regions and people. Within a unified Europe, with increasing international and trans-border co-operation and increasing common environmental problems, the creation of a specific European Association for Landscape Ecology (IALE-Europe), in addition to the existing international association and its national chapters, became justified by the need for a collaborative endeavour to address the specific problems of landscapes in Europe and to stimulate cooperation between landscape ecologists in research, education and practice.